Karapan Sapi Tangghe' cultural tourism attraction local wisdom in Madura - Zali, Moh; A. Yudi Heryadi; Malikah Umar; Selvia Nurlaila; Bambang Kurnadi; Abu Amar; Ach Ahdafil Aman (Jurnal Ternak, 2025)
This study aims to understand the meaning, role, and potential of tangghe cow racing tradition in Madura as a cultural tourist attraction as well as economic opportunities based on local wisdom. The research approach used is qualitative with case study design that focuses on Langsar Village, Saronggi District, Sumenep regency. Data were obtained through in-depth interviews, participatory observations, and documentation, and analyzed using Miles and Huberman interactive models through the stages of data reduction, data presentation, and verification. The results showed that the bull race tangghe ' is not only seen as a race, but also as a symbol of identity and pride of the Madurese community. This tradition has a considerable tourist attraction because it attracts audiences from various regions, so it has the potential to be developed as a leading cultural tourist attraction. In addition, tangghe’ bull race has a positive economic impact on the community through trading activities, services, and rental of cattle and race equipment. Local wisdom values such as mutual cooperation, solidarity, and village Honor are maintained in the practice of this tradition. However, there are challenges in the form of stigma of violence in traditional Bull Racing, which can be minimized by promoting the tangghe’ model as a revitalization of non-violent culture. This study concludes that karapan sapi tangghe’ can be developed as a sustainable cultural tourism that is aligned with ethical values, religious norms, and animal welfare, while contributing to the improvement of the local economy.